Turning a burden into an opportunity: Pennycress (Thlaspi arvense L.) a new oilseed crop for biofuel production. (November 2019) - Zanetti, Federica; Isbell, Terry A.; Gesch, Russ W.; Evangelista, Roque L.; Alexopoulou, Efthymia; Moser, Bryan; Monti, Andrea
Abstract: Recently, an "old weed", pennycress ( Thlaspi arvense L.) has become an attractive non-food oilseed crop for Europe and the USA. Pennycress can be produced with existing farm equipment and infrastructure while being grown in the off-season between conventional commodity crops. The adaptation to marginal lands and the satisfactory seed yields make pennycress a viable alternative feedstock for biofuels. In the last decade, pennycress has been extensively studied as a potential oilseed crop in the USA, while receiving far less attention in Europe. Differences in climate and agricultural management between USA and Europe may not permit direct translation of pennycress agronomic knowledge across diverse environments. In the present study, sowing date and seeding rate of pennycress were evaluated in different European (Italy and Greece) and US (Minnesota and Illinois) locations to optimize site-specific production, and determine environmental influence on pennycress-derived biofuel. Pennycress productivity increased with seeding rate up to 1500 m −2 in Europe, but only to 672 m −2 in USA, while sowing in early autumn always improved yields. Seed yield of about 1 Mg ha-1 was achieved only in Greece, where adequate precipitation during the growing season was available. Seed yields were 250% and 140% higher in Greece and Italy, respectively, than Minnesota. Pennycress oil was suitable to convert into biofuel and its composition was influenced by growing environment. In Greece, polyunsaturated fatty acid content was 6% compared to Italy and Illinois. However, the oxidative stability of pennycress oil needs improvement to meet EU and US standards for biodiesel. Highlights: Pennycress grew well and provided satisfactory seed yields in all test environments. Pennycress growth and productivity are highly influenced by specific environmental conditions. Pennycress productivity was improved by increased seeding rate and early sowing. Pennycress oil is a valuable raw material for conversion into biodiesel. Pennycress biodiesel can complement the typical raw-materials used in Europe and USA.